Relationship between Zinc (Zn2+) and Glutamate Receptors in the Processes Underlying Neurodegeneration - Bartłomiej Pochwat; Gabriel Nowak; Bernadeta Szewczyk (Neural Plasticity)
The results from numerous studies have shown that an imbalance between particular neurotransmitters may lead to brain circuit dysfunction and development of many pathological states. The significance of glutamate pathways for the functioning of the nervous system is equivocal. On the one hand, glutamate transmission is necessary for neuroplasticity, synaptogenesis, or cell survival, but on the other hand an excessive and long-lasting increased level of glutamate in the synapse may lead to cell death. Under clinical conditions, hyperactivity of the glutamate system is associated with ischemia, epilepsy, and neurodegenerative diseases such as Alzheimer’s, Huntington’s, and many others. The achievement of glutamate activity in the physiological range requires efficient control by endogenous regulatory factors. Due to the fact that the free pool of ion Zn2+ is a cotransmitter in some glutamate neurons; the role of this element in the pathophysiology of a neurodegenerative diseases has been intensively studied. There is a lot of evidence for Zn2+ dyshomeostasis and glutamate system abnormalities in ischemic and neurodegenerative disorders. However, the precise interaction between Zn2+ regulative function and the glutamate system is still not fully understood. This review describes the relationship between Zn2+ and glutamate dependent signaling pathways under selected pathological central nervous system (CNS) conditions.